Case Report: A patient with the rare third-generation TKI-resistant mutation EGFR L718Q who responded to afatinib plus cetuximab combination therapy - Zhang, Guoqing; Yan, Beibei; Guo, Yanan; Yang, Hang; Li, Xiangnan; Li, Jindong (Frontiers in Oncology, 2022)
Third-generation tyrosine kinase inhibitors (TKIs), such as osimertinib, almonertinib and furmonertinib, overcome the mechanisms of resistance to first-generation inhibitors (such as gefitinib, erlotinib and icotinib) by incorporating an acrylamide group that alkylates the Cys797 of EGFR T790M. However, drug resistance is inevitable, even for third-generation TKIs. Screening for drug-resistant mutations by repeat biopsy and repeat gene sequencing is necessary after TKI treatment. Among various third-generation TKI-resistant mutations, secondary mutation of the L718 residue of EGFR exon 18 was found in approximately 8% of patients and is responsible for drug resistance in vitro and in vivo. Furthermore, there is limited clinical experience of targeted therapy for this mutation. Herein, we report for the first time that afatinib and cetuximab combination therapy can overcome such drug resistance.